MASLAHAH AND THEIR RELATIONSHIP WITH LEGAL ISTINBAT, (STUDY OF AL-JUWAYNI THOUGHT IN THE BOOK OF AL-BURHAN FI PROPOSED AL-FIQH) - Abdul Rasyid Ridho (Universitas Islam Negeri Mataram, 2019)
Maslahah in al-Juwayni's thinking is not a source of law, but it is an indicator in determining the existence of a law. Basically, maslahah which is the basis and purpose of the establishment of sharia, in the view of al-Juwayni, concerns all universal human needs that can guarantee the maintenance and uphold of human life's milestones. This is al-Juwayni's formulation includes four things, namely guaranteed the maintenance of religion, soul, honor (ancestry), and human property. Then in making istinbat a law, especially related to cases that have not been regulated by the legal status, it must refer to the five categories of maslahah as formulated by al-Juwayni. These five categories are the basis and purpose of the making and determination of the law found in the text.